Brain Activity Underlying Muscle Relaxation - Kato, Kouki; Vogt, Tobias; Kanosue, Kazuyuki (Frontiers in Physiology, 2019)
Fine motor control of not only muscle contraction but also muscle relaxation is required for appropriate movements in both daily life and sports. Movement disorders such as Parkinson’s disease and dystonia are often characterized by deficits of muscle relaxation. Neuroimaging and neurophysiological studies suggest that muscle relaxation is an active process requiring cortical activation, and not just the cessation of contraction. In this article, we review the neural mechanisms of muscle relaxation, primarily utilizing research involving transcranial magnetic stimulation (TMS). Several studies utilizing single pulse TMS have demonstrated that, during the relaxation phase of a particular muscle, the excitability of the corticospinal tract controlling that particlar muscle is more suppressed than in the resting condition. Other studies, utilizing paired-pulse TMS, have shown that the intra-cortical inhibition is activated just before muscle relaxation. Moreover, muscle relaxation of one body part suppresses cortical activities controlling other body parts in different limbs. Therefore, the cortical activity might not only be a trigger for muscle relaxation of the target muscles but could also bring about an inhibitory effect on other muscles. This spread of inhibition can hinder the appropriate contraction of muscles involved in multi-limb movements such as those used in sports and the play of musical instruments. This may also be the reason why muscle relaxation is so difficult for beginners, infants, elderly, and the cognitively impaired.